Integration and commissioning of the ATLAS Muon-to-Central-Trigger-Processor Interface for Run-3. (1st April 2022) - Perrella, S.; Afik, Y.; Armbruster, A.; Czodrowski, P.; Ellis, N.; Haas, S.; Koulouris, A.; Kulinska, A.M.; Marzin, A.; Pauly, T.; Ryjov, V.; Sanfilippo, L.; et al.
Abstract: The Muon-to-Central Trigger Processor Interface was completely redesigned as part of the ATLAS Level-1 trigger upgrade for Run 3 of the Large Hadron Collider. The new system is implemented as a single AdvancedTCA module, using three large state-of-the-art FPGAs and high-density fiber-optic modules. Trigger information from the muon trigger detectors are received through 208 high speed links, while 60 links are used to send processed trigger information to the L1 Topological Trigger Processor and the Central Trigger Processor. Extensive integration tests with all input and output systems have shown that the data transfer is stable and reliable. We present results from integration tests with connected sub-systems as well as commissioning of the Muon-to-Central Trigger Processor Interface in the ATLAS experiment.